Case report: A study on the de novo KMT2D variant of Kabuki syndrome with Goodpasture's syndrome by whole exome sequencing - Shuolin Li; Jing Liu; Yuan Yuan; Aizhen Lu; Fang Liu; Li Sun; Quanli Shen; Libo Wang (Frontiers Media S.A., 2022)
Kabuki syndrome (KS) is a rare genetic disorder characterized by dysmorphic facial features, skeletal abnormalities, and intellectual disability. KMT2D and KDM6A were identified as the main causative genes. To our knowledge, there exist no cases of KS, which were reported with pneumorrhagia. In this study, a 10-month-old male was diagnosed to have KS with typical facial features, skeletal anomalies, and serious postnatal growth retardation. Whole exome sequencing of the trio family revealed the presence of a de novo KMT2D missense variant (c.15143G > A, p. R5048H). The child was presented to the pediatric emergency department several times because of cough, hypoxemia, and anemia. After performing chest CT and fiberoptic bronchoscopy, we found that the child had a pulmonary hemorrhage. During research on the cause of pulmonary hemorrhage, the patient's anti-GBM antibodies gradually became positive, and the urine microalbumin level was elevated at the age of 12-month-old. After glucocorticoids and immunosuppressant therapy, the patient became much better. But he had recurrent pulmonary hemorrhage at the age of 16 months. Therefore, the patient underwent digital subtraction angiography (DSA). However, the DSA showed three abnormal bronchial arteries. This single case expands the phenotypes of patients with KS and Goodpasture's syndrome, which were found to have a de novo KMT2D missense variant.